LKMA FINANCIAL ADMININTRATION APPLICATION SYSTEM IN BUMI RATU VILLAGE BASED ON VISUAL BASIC - Sugi yanto (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
This study aims to analyze the financial system Gapoktan Karya Manunggal in the village of Bumi Ratu District Pagelaran Pringsewu. Basically, Gapoktan Karya Manunggal is a combination of several farmer groups and run a business together. With the help of the government is a racing program then Gapoktan Karya Manunggal menjalankn other businesses to the business of rural agribusiness finance institutions (LKMA). But now Gapoktan Karya Manunggal progressed so that Gapoktan Karya Manunggal opened business units such as savings and loan units and fertilizer sales unit. Management of administrative system in Gapoktan manunggal work is still done manually with a very limited number of Gapoktan board. This led to the slow performance of the cooperative and allowed the occurrence of errors that are not desired by the board of Gapoktan. Therefore, a new system is more efficient in reducing this problem. The system developed is a system of saving and loan application, recording, and calculating the net income, and selling of fertilizer. The design of this application is made for the purpose of facilitating the administrators Gapoktan in monitoring the existing finances without having to check every manual written by Gapoktan board in the village of Bumi Ratu.